Pengaruh Perbandingan Terigu Dengan Puree Labu Kuning (Cucurbita moschata) Terhadap Karakteristik Kue Nastar - Priyatna Putra, I Gede; Timur Ina, Putu; Indri Hapsari Arihantana, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 1 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i01.p06, 2021)
This research aims to determine the effect of the comparison of wheat flour with puree of pumpkin on the characteristics of nastar cake and to find out the right comparison of wheat flour with puree of pumpkin to produced nastar cake with the best characteristics. The experimental design used in this research was a Completely Randomized Design (CRD) with a comparison of wheat flour and puree of pumpkin consisting of 5 treatments namely 100% : 0%, 95% : 5%, 90% : 10%, 85% : 15%, and 80% : 20%. All treatments were repeated four times so that they were obtained 20 experimental units. The data obtained were analyzed by variance and if the treatment had significant effect then followed by Duncan’s Multiple Range Test. The results showed that the comparison of wheat flour and puree of pumpkin had a significant effect on the water content, total carotene content, antioxidant activity (?-carotene bleaching), color, texture, flavor, taste, and overall acceptance. Ratio of 80% wheat flour and 20% puree of pumpkin had the best characteristics with water content of 2.55%, ash content of 0.75%, ?-carotene content of 4.63 mg/100g, antioxidant activity of 1.71 mg/ml, color liked, texture rather liked, flavor liked, taste liked, and overall acceptance liked.